Credit Surety Fund: A credit innovation for micro, small, and medium-sized enterprises in the Philippines - Gary V. Maningo (Asian Development Bank Institute (ADBI), 2016)
Micro, small, and medium-sized enterprises are a backbone of the Philippine economy. One factor that hinders the growth of these enterprises is their difficulty in accessing finance from banks and other financial institutions. The Credit Surety Fund (CSF) was established to help these enterprises and other organizations become creditworthy and bankable. The CSF is a credit guarantee program initiated by the Bangko Sentral ng Pilipinas that enables enterprises and cooperatives to gain easier access to loans from banks without providing collateral. The CSF pools contributions from cooperatives and nongovernment organizations, local government units, institutions such as the Development Bank of the Philippines, the Land Bank of the Philippines, the Industrial Guarantee and Loan Fund, and other organizations. In this way, it is a public-private partnership that links the key players of the economy to empower enterprises and cooperatives.
Keywords: G21; G24; G32; 330; Credit Surety Fund; public-private partnerships; credit innovation; credit guarantee programs